Optimalisasi instagram sebagai daya dukung KPuK Malang dalam edukasi publik melalui sosial media - Andika Ryan Saputra; Ari Selviana Rahmi; Irma Amnita Surya Listya Ningsih; Nurma Sekar Pratiwi (Altruis: Journal of Community Services, 2022)
Instagram is one of the social media that is currently growing rapidly. Optimal use of Instagram can provide positive benefits for users, and organizations are no exception. The initial findings obtained from Women’s Coalition for Leadership (KPuK) are that they still have not utilized the features on Instagram optimally. Two features that have not been utilized are the insight feature and the use of bio-Instagram. Based on these findings, the Service Team then continued to become an Instagram social media optimization program as a support for public education. The methods used to support this program include the planning stage, the implementation stage, and the evaluation stage. Furthermore, at the data collection stage, theService Team used data collection techniques of observation, interviews, and FGDs to collect data prior to program development. The results of this program make Instagram more active by utilizing the insight feature. In addition, by creating a database of KPuK products and placing them on bio-Instagram, it makes it easy for the public to access products about gender disparities. The success of the program can be seen from the availability of partners to continue the program that has been established.